Persistence of Suspected Probiotic Organisms in Preterm Infant Gut Microbiota Weeks After Probiotic Supplementation in the NICU - Yousuf, Efrah I.; Carvalho, Marilia; Dizzell, Sara E.; Kim, Stephanie; Gunn, Elizabeth; Twiss, Jennifer; Giglia, Lucy; Stuart, Connie; Hutton, Eileen K.; Morrison, Katherine M.; Stearns, Jennifer C. (Frontiers in Microbiology, 2020)
Probiotics are becoming a prevalent supplement to prevent necrotizing enterocolitis in infants born preterm. However, little is known about the ability of these live bacterial supplements to colonize the gut or how they affect endogenous bacterial strains and the overall gut community. We capitalized on a natural experiment resulting from a policy change that introduced the use of probiotics to preterm infants in a single Neonatal Intensive Care Unit. We used amplicon sequence variants (ASVs) derived from the v3 region of the 16S rRNA gene to compare the prevalence and abundance of Bifidobacterium and Lactobacillus in the gut of preterm infants who were and were not exposed to a probiotic supplement in-hospital. Infants were followed to five months corrected age. In the probiotic-exposed infants, ASVs belonging to species of Bifidobacterium appeared at high relative abundance during probiotic supplementation and persisted for up to 5 months. In regression models that controlled for the confounding effects of age and antibiotic exposure, probiotic-exposed infants had a higher abundance of the suspected probiotic bifidobacteria than unexposed infants. Conversely, the relative abundance of Lactobacillus was similar between preterm groups over time. Lactobacillus abundance was inversely related to antibiotic exposure. Furthermore, the overall gut microbial community of the probiotic-exposed preterm infants at term-corrected age clustered more closely to samples collected from 10-day old full-term infants than to samples from unexposed preterm infants at term age. In conclusion, routine in-hospital administration of probiotics to preterm infants resulted in the potential for colonization of the gut with probiotic organisms post-discharge and effects on the gut microbiome as a whole. Further research is needed to fully discriminate probiotic bacterial strains from endogenous strains and to explore their functional role in the gut microbiome and in infant health.